Optimizing Training Management Through Long-Term Athlete Development (LTAD) Framework (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community development is intended to assess the effectiveness of a 12-week training management approach grounded in the Long-Term Athlete Development (LTAD) framework, executed at the Surabaya Athletes Association. The program aims to improve athletic performance while comprehensively addressing the developmental requirements of student-athletes. Thirty student-athletes, aged 13 to 17 years, engaged in the 12-week intervention. A mixed-method research methodology was utilized to perform a thorough study. Quantitative data were obtained using pre- and post-program physiological evaluations (VO2Max, strength, agility), while qualitative data were collected through surveys assessing motivation and program satisfaction. The quantitative study demonstrated a statistically significant enhancement in participants' VO2Max values (p